PENGEMBANGAN MODUL BIMBINGAN KELOMPOK DENGAN TEKNIK EFT (EMOTIONAL FREEDOM TECHNIQUE) UNTUK MENGATASI STRES AKADEMIK SISWA KELAS VIII SMPN 1 DARANGDAN - Amira Nur Fajar; Siti Fatimah; Devy Sekar Ayu Ningrum (IKIP Siliwangi, 2023)
The purpose of this research is to assist students in overcoming their academic stress using a group guidance module with the EFT (Emotional Freedom Technique) technique. This research uses research and development (R&D) methods using the Borg and Gall model. The sample used in this study were 8 students of class VIII SMPN 1 Darangdan. The results showed that the product developed at SMPN 1 Darangdan, namely the development of group guidance module media with the EFT (Emotional Freedom Technique) technique to overcome students' academic stress was very feasible to use, this is in line with the results of expert practitioner validation which is 90%